The influence of blended learning using the science technology society approach on learning independence - Nuril Huda; Windi Setiawan; H. Haerussaleh (Universitas Muhammadiyah Malang, 2024)
Independent learning facilitates students in improving their competencies according to the challenges of the current era. However, learning in schools often does not empower students to become independent learners. This research aims to find out whether the application of blended learning with the Science Technology Society (STS) approach can increase student independence in learning or not. This research is quantitative. The sample for this research was students from the informatics engineering and communication science study program at Dr Soetomo University. The instrument used in this research was a questionnaire. Questionnaires are used to find out information about independence. Data analysis involved conducting normality and homogeneity tests, followed by an independent sample test. The results of the analysis suggest an influence of blended learning with an STS approach on learning independence in higher education (t = 21.246, p < 0.001), implying the potential effectiveness of integrating STS principles into educational practices to foster greater autonomy among students.